Simulation and Real-Time Implementation of MPPT Techniques for PV System using High Precision PV Emulator and dSPACE DS1202 MicroLabBox - Srishti; Gaur, Prerna (International Journal of Computer Sciences and Engineering, 2019)
The Maximum Power Point Tracking (MPPT) is a vital element in a Photovoltaic (PV) system to harvest maximum power from solar PV system. Therefore, it is of interest to us to develop a more effective and efficient system that can transfer maximum power to the load. Implementation of the new MPPT techniques such as Artificial Neural Network (ANN), Fuzzy Logic Control (FLC) and Cuckoo Search Algorithm (CSA) is carried out to identify the most efficient system and the results are compared with conventional Perturb and Observe (P&O) and are presented in this paper. The proposed models are simulated and obtained results are analyzed and compared with the conventional method using MATLAB/Simulink, while the real-time implementation of similar prototype is carried out using a novel dSPACE DS1202 MicroLabBox and highly accurate PV emulator. Further this paper also comprises the comparison of steady state accuracy of D.C. link voltage of proposed techniques i.e. ANN, FLC, CSA vis-a-vis conventional P&O using MATLAB/Simulink and dSPACE.